2018
DOI: 10.3390/w10101373
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Long-Term Reference Evapotranspiration and Its Components over the Korean Peninsula

Abstract: In this study, the spatial and temporal trends of reference evapotranspiration (ETo) and its components consisting of the energy term (ENo) and the aerodynamic term (AEo) were considered over the Korean Peninsula. The T-test and Mann–Kendall (MK) test were used to detect parameter trends after removing the effect of serial correlation from annual and seasonal time series between 1980 and 2017. Due to the lack of solar-radiation data for North Korea (NK), a regionally calibrated model based on South Korea (SK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Both non-parametric (Mann-Kendall test) [32,33] and parametric (linear regression analysis) procedures are used to identify the annual and seasonal trends. The Mann-Kendall (MK) statistical test is used worldwide to detect the trend of precipitation, temperature, and relative humidity [14,[34][35][36][37]. The non-parametric tests are preferred as they are more suitable for non-normally distributed data, which are frequently encountered in hydro-meteorological time series [38].…”
Section: Trends Of Hydrological Variablesmentioning
confidence: 99%
“…Both non-parametric (Mann-Kendall test) [32,33] and parametric (linear regression analysis) procedures are used to identify the annual and seasonal trends. The Mann-Kendall (MK) statistical test is used worldwide to detect the trend of precipitation, temperature, and relative humidity [14,[34][35][36][37]. The non-parametric tests are preferred as they are more suitable for non-normally distributed data, which are frequently encountered in hydro-meteorological time series [38].…”
Section: Trends Of Hydrological Variablesmentioning
confidence: 99%
“…Wind flows likely exchange the moist air very quickly with dry air, notably during spring and winter in our study area ( Figure 2), and makes ET 0 more sensitive to u z during these periods in comparison with other seasons (Ghafouri-Azar et al, 2018) (Figure 3). In general, for both sites, the sensitivity of ET 0 to climatic variables was more significant during October and May.…”
Section: Et 0 Affected Most By T Max and N During Warm Period And Rh mentioning
confidence: 93%
“…where h is the height of the measurement above the ground surface (m) and u z is the measured wind (m s -1 ). Also for standardization, T for 24-hour periods is defined as the mean of the daily maximum (T max ) and minimum temperatures (T min ) rather than as the average of hourly temperature measurements (FAO, 1998).…”
Section: Reference Evapotranspirationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported both increasing and decreasing trends in Iran (Dinpashoh et al 2011), China (Mo et al 2017;Liu et al 2020), and India (Sonali & Nagesh Kumar 2016). Significant increasing trends of ET 0 were reported in the Korean Peninsula (Ghafouri-Azar et al 2018), in Iran (Azizzadeh & Javan 2015), in central Europe (Zaninović& Gajic-Čapka 2000), and China (Niu et al 2019). The strong decreasing trend in ET 0 was observed in Canada (Burn & Hesch 2007), in the United States (Golubev et al 2001), in Australia (Donohue et al 2010), in India (Verma et al 2008;Jhajharia et al 2012;Yadav et al 2016;Goroshi et al 2017), and in China (Niu et al 2019).…”
Section: Introductionmentioning
confidence: 98%